Pengujian staphylococus aureus pada daging ayam beku yang dilalulintaskan melalui pelabuhan penyeberangan merak - K.T. Palupi .; M.W.Adiningsih .; T.Sunartatie .; U. Afifi .; T. Purnawarman . (Hemera Zoa, 2010)
This study was aimed to test Staphylococcus aureus in frozen chicken meat as an indicator of quality and poultry slaughter house hygiene. Thirty two samples of frozen chicken meats transported through Merak port were taken from Cilegon 2 nd Class Agricultural Quarantine Installation. Those samples came from DKI Jakarta (11 samples), Bekasi (6 samples), Bogor (4 samples) and Serang (11 samples). Number of S. aureus in frozen chicken meat was conducted with plate count method using baird parker agar (BPA) media. The result showed that the average number of S. aureus in Serang was the highest (5.4x102±6.73x102 cfu/g). In the other hand, Bekasi had the lowest average number of S. aureus (0.60x102±0.38x 102  cfu/g ). From the four areas, there were samples which over the maximum limit of S.aureus as permitted in SNI 01-7388-2009 (1x102  cfu/g ) with an avarege proportion about 35.42%.